Microbial reduction in wastewater treatment using Fe3+ and Al3+ coagulants and PAA disinfectant - Pradhan, Surendra K.; Kauppinen, A.; Martikainen, K.; Pitkanen, T.; Kusnetsov, J.; Miettinen, I.T.; Pessi, M.; Poutiainen, H.; Heinonen-Tanski, H. (IWA Publishing, 2013)
Wastewater is an important source of pathogenic enteric microorganisms in surface water and a major contaminating agent of drinking water. Although primary and secondary wastewater treatments reduce the numbers of microorganisms in wastewater, significant numbers of microbes can still be present in the effluent. The aim of this study was to test the feasibility of tertiary treatment for municipal wastewater treatment plants (WWTPs) using PIX (FeCl3) or PAX (AlCl3) coagulants and peracetic acid (PAA) the disinfectant to reduce microbial load in effluent. Our study showed that both PIX and PAX efficiently reduced microbial numbers. PAA disinfection greatly reduced the numbers of culturable indicator microorganisms (Escherichia coli, intestinal enterococci, F-specific RNA coliphages and somatic DNA coliphages). In addition, pathogenic microorganisms, thermotolerant Campylobacter, Salmonella and norovirus GI, were successfully reduced using the tertiary treatments. In contrast, clostridia, Legionella, rotavirus, norovirus GII and adenovirus showed better resistance against PAA compared to the other microorganisms. However, interpretation of PCR analysis results will need further studies to clarify the infectivity of the pathogenic microbes. In conclusion, PIX and PAX flocculants followed by PAA disinfectant can be used as a tertiary treatment for municipal WWTP effluents to reduce the numbers of indicator and pathogenic microorganisms.